Consumer based brand equity in the 21st century: an examination of the role of social media marketing. Issue 3 (15th August 2016) - Yazdanparast, Atefeh; Joseph, Mathew; Muniz, Fernanda
Abstract : Purpose: The present research investigates the influence of brand-based social media marketing (SMM) activities on metrics of consumer-based brand equity (CBBE). Specifically, the study examines the role of consumer-brand social media experiences on attitude toward SMM activities of brands and its consequent impact on brand perceptions. Design/methodology/approach: Paper-and-pencil surveys were administered to undergraduate students in a Southwestern university in exchange for extra credit. Survey questions were adapted from previously validated scales, and measurement adaptations were minimal and only related to the context of questions to assure their relevance with the context of this study. Bi-variate correlation, bootstrapping technique, Sobel test, ANOVA and linear regression were used to test the hypotheses. Findings: The results indicate that brand-based SMM is essential in impacting consumers' attitudes toward brands and consequently, CBBE reflected via perceived value for the cost, perceived uniqueness and the willingness to pay a price premium for a brand. Additionally, the main reason for individuals to use social media impacts their attitudes toward and receptiveness of SMM activities of brands. Research limitations/implications: This study used a sample of college students to address the research questions. Considering the higher adoption rate and interest in social media among younger consumer groups, the results may not be representative of the entire population. Much of the existing research on social media, however, has focused on undergraduate college students and is primarily based on studies utilizing the similar research population. Originality/value: The present research is one of the few studies that empirically examine the impact of consumer-brand interactions/experiences on consumers' attitudes toward SMM activities of brands, as well as brand-related knowledge and perceptions as reflected by CBBE. The results indicate that the CBBE model of the twenty-first century should incorporate the role of brand-based SMM activities as facilitators of brand knowledge (i.e. brand awareness and brand image) by reinforcing or even shaping important brand-based associations.